cDNA cloning and 1.75 Å crystal structure determination of PPL2, an endochitinase and N-acetylglucosamine-binding hemagglutinin from Parkia platycephala seeds - Cavada, Benildo S.; Moreno, Frederico B. B. [UNESP]; Da Rocha, Bruno A. M.; De Azevedo Jr., Walter F.; Castellón, Rolando E. R.; Goersch, Georg V.; Nagano, Celso S.; De Souza, Emmanuel P.; Nascimento, Kyria S.; Radis-Baptista, Gandhi; Delatorre, Plínio; Leroy, Yves; et al. (Wiley, 2006)
Parkia platycephala lectin 2 was purified from Parkia platycephala (Leguminosae, Mimosoideae) seeds by affinity chromatography and RP-HPLC. Equilibrium sedimentation and MS showed that Parkia platycephala lectin 2 is a nonglycosylated monomeric protein of molecular mass 29 407 ± 15 Da, which contains six cysteine residues engaged in the formation of three intramolecular disulfide bonds. Parkia platycephala lectin 2 agglutinated rabbit erythrocytes, and this activity was specifically inhibited by N-acetylglucosamine. In addition, Parkia platycephala lectin 2 hydrolyzed β(1-4) glycosidic bonds linking 2-acetoamido-2-deoxy-β-d-glucopyranose units in chitin. The full-length amino acid sequence of Parkia platycephala lectin 2, determined by N-terminal sequencing and cDNA cloning, and its three-dimensional structure, established by X-ray crystallography at 1.75 Å resolution, showed that Parkia platycephala lectin 2 is homologous to endochitinases of the glycosyl hydrolase family 18, which share the (βα) 8 barrel topology harboring the catalytic residues Asp125, Glu127, and Tyr182. © 2006 The Authors.
Keywords: Endochitinase; Glycosyl hydrolase family 18; Mimosoideae; Parkia platycephala; X-ray crystal structure; chitin; chitinase; complementary DNA; endochitinase; genomic DNA; glycosidase; hemagglutinin; lectin; lectin 2; n acetylglucosamine; RNA; unclassified drug; affinity chromatography; amino acid composition; amino acid sequence; animal cell; anion exchange chromatography; controlled study; crystal structure; disulfide bond; enzyme activity; enzyme analysis; enzyme inhibition; enzyme purification; erythrocyte; hemagglutination; legume; matrix assisted laser desorption ionization time of flight mass spectrometry; molecular cloning; molecular weight; nonhuman; polyacrylamide gel electrophoresis; priority journal; rabbit; reversed phase high performance liquid chromatography; RNA isolation; sedimentation; X ray crystallography; Acetylglucosamine; Amino Acid Sequence; Base Sequence; Chitinase; Cloning, Molecular; Crystallization; Crystallography, X-Ray; DNA, Complementary; Fabaceae; Hemagglutinins; Molecular Sequence Data; Plant Lectins; Protein Binding; Seeds; Oryctolagus cuniculus